Woda święcona (pobłogosławiona) jako wyraz powszechnego kapłaństwa wiernych - Bachanek, Grzegorz (Collectanea Theologica, 2018)
Holy water can help lay people in their pursuit of sainthood. It reminds them about the sacrament of baptism and encourages to be grateful to God for such a great gift, to feel joy and pride in being Christian. It helps to prepare for the Eucharist and raises awareness God’s presence. Through holy water God absolves the venial sins when we use it in the spirit of remorse. This water constitutes an element of the blessing which is given by parents to their children on the basis of priesthood arising from the mystery of baptism. It plays an important role in the Christian customs related to burial, indicating the exceptional meaning of human death, the dignity of the human body, the mystery of the purgatory and the significance of the prayer for the dead. Holy water is used in blessings and shows the need to sanctify the whole human life, the everyday existence, the various dimensions of human labour and activity. Sometimes it is kept in the houses of the believers to which they can resort to in moments of temptation. Many saints talks of the importance of holy water as protection from the evil spirit. Furthermore, it provides consolation, reassurance in spiritual struggle and internal renewal. There is also the danger of abuse: mechanical use, giving up the spiritual struggle with venial sins, neglecting everyday duties, magical thinking.